Health Risks and Adverse Reactions to Functional Foods. Issue 2 (25th January 2016) - Ameratunga, Rohan; Crooks, Christine; Simmons, Greg; Woon, See-Tarn
Abstract : Functional foods have become increasingly popular with consumers anxious to mitigate the effects of an unhealthy lifestyle or aging. In spite of attractive health claims, these products do not have legal or regulatory status in most countries and are regulated through their health claims. Regulation of functional foods by health claims does not address health risks and adverse effects of these products. In this essay regulatory aspects of functional foods are reviewed along with adverse effects published in the peer-reviewed literature. We detail why the lack of an internationally accepted definition of functional foods places consumers at risk of adverse outcomes. Our review will assist regulatory agencies, manufacturers and consumer groups to assess the benefits and reduce the risks associated with these products.